Fishing with skis, digging with noodles: Resolving task-and-tool mismatches in efforts to advance health equity - Katrina Plamondon; Sana Z. Shahram (Elsevier, 2024)
When it comes to advancing equity, across the health sciences, efforts repeatedly target interventions on those most burdened by inequities rather than the systems or structures that give rise to inequities. This mismatch, in and of itself, is an important determinant of equity. While many conceptual models draw collective attention to deeper, structural causes (e.g., social, political, and commercial determinants of health) as the 'what', inattention to questions of 'how'-or the collective practices that serve to connect what is known with what is done-are like a wedge holding this gap in place. In this article, we use an exaggerated metaphor of mismatched task-and-tool to provoke critically reflective dialogue about collective attachment to scholarship and practices incoherent with our own body of knowledge. We offer a set of five practices easily integrated in any aspect of work related to advancing equity, through everyday actions anyone (anywhere) can take to purposefully act from an evidence and equity-informed position.